PENGARUH PENDIDIKAN KEUANGAN DI KELUARGA, PEGETAHUAN KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN - Adhi Widyakto; Dwi Murtini; Risti Ulfi Hanifah; Aprih Santoso (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of financial education in the family, financial knowledge and lifestyle on financial behavior in Management students of the Faculty of Economics, Semarang University Class of Employees 2019/2020. The sample in this study used a purposive sampling method approach. Purposive sampling is a data sampling technique based on certain considerations. The sample in this study amounted to 119 respondents.This study uses quantitative data types and the data source used is primary data. The data analysis technique was carried out with the help of SPSS version 26, the analytical methods used included descriptive analysis, validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test and multiple linear regression test. Testing the hypothesis by t test (test), while testing the model by testing the coefficient of determination.The results showed that financial education in the family had a significant positive effect on financial behavior, financial knowledge had a significant positive effect on financial behavior, and lifestyle had a significant positive effect on financial behavior